Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa Kelas V SDN 77 Parepare - Musfirah Musfirah; Muslimin Muslimin; Hasmiani Hasmiani (STKIP Andi Matappa Pangkep, 2023)
This research is a classroom action research which are to determine the process of applying the problem based learning model to about material heat transfer in Class V and to determine the improvement of learning achievement in science subjects about heat transfer by applying the problem based learning model. The approach used in this study is a qualitative approach. Data collection techniques used are observation, tests, and documentation. The research subjects were class teachers and students, totaling 21 students and 1 teacher. The research was carried out in two cycles. In the first cycle the research results on the learning process were in good qualification (B) and the learning test results were in sufficient qualification (C). While in the second cycle the research results on the learning process were in good qualification and (B) the results of the learning and learning test were in good qualification (B). The conclusion of this research is that the application of problem based learning (pbl) model on heat transfer material can improve the learning process and learning outcomes of students in class V UPTD SD Negeri 77 Parepare.